The molecular characteristics of high-grade gastroenteropancreatic neuroendocrine neoplasms - Venizelos, Andreas; Elvebakken, Hege; Perren, Aurel; Nikolaienko, Oleksii; Deng, Wei; Lothe, Inger Marie B; Couvelard, Anne; Hjortland, Geir Olav; Sundlöv, Anna; Svensson, Johanna; Garresori, Harrish; Kersten, Christian; et al. (Endocrine-related cancer, 2022)
High-grade (HG) gastroenteropancreatic (GEP) neuroendocrine neoplasms (NEN) are rare but have a very poor prognosis and represent a severely understudied class of tumours. Molecular data for HG GEP-NEN are limited, and treatment strategies for the carcinoma subgroup (HG GEP-NEC) are extrapolated from small-cell lung cancer (SCLC). After pathological re-evaluation, we analysed DNA from tumours and matched blood samples from 181 HG GEP-NEN patients; 152 neuroendocrine carcinomas (NEC) and 29 neuroendocrine tumours (NET G3). Based on the sequencing of 360 cancer-related genes, we assessed mutations and copy number alterations (CNA). For NEC, frequently mutated genes were TP53 (64%), APC (28%), KRAS (22%) and BRAF (20%). RB1 was only mutated in 14%, but CNAs affecting RB1 were seen in 34%. Other frequent copy number losses were ARID1A (35%), ESR1 (25%) and ATM (31%). Frequent amplifications/gains were found in MYC (51%) and KDM5A (45%). While these molecular features had limited similarities with SCLC, we found potentially targetable alterations in 66% of the NEC samples. Mutations and CNA varied according to primary tumour site with BRAF mutations mainly seen in colon (49%), and FBXW7 mutations mainly seen in rectal cancers (25%). Eight out of 152 (5.3%) NEC were microsatellite instable (MSI). NET G3 had frequent mutations in MEN1 (21%), ATRX (17%), DAXX, SETD2 and TP53 (each 14%). We show molecular differences in HG GEP-NEN, related to morphological differentiation and site of origin. Limited similarities to SCLC and a high fraction of targetable alterations indicate a high potential for better-personalized treatments.